Formulation of hybrid 3D image segmentation algorithm based partial differential equation - Aboaba, A. A.; Hameed, Shihab A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha; Chowdhury, Md. Sazzad Hossien (2012)
Segmentation is an important tool for analysis and understanding of most images encountered in science and engineering. One of the best segmentation methods that can perform 3D segmentation is the level-set method which has its mathematical foundation in partial differential equation (PDE). Owing to its complex nature, it exhibits a level of unacceptable sluggishness on implementation hence a need to hasten up the process by hybridizing it with a faster region-based segmentation method which is inherently a logical approach to segmentation pivoted on thresholding but not as good in segmentation as the former. This work presents a mathematical hybrid of the two methods that is hoped to produce a better segmentation result.